Effects of Postmortem Interval on Biomolecule Integrity in the Brain. Issue 5 (May 2015) - Nagy, Corina; Maheu, Marissa; Lopez, Juan Pablo; Vaillancourt, Kathryn; Cruceanu, Cristiana; Gross, Jeffrey A.; Arnovitz, Mitchell; Mechawar, Naguib; Turecki, Gustavo
<x xml:space="preserve">Abstract</x> Abstract Postmortem brain research is invaluable to the study of neurologic and neuropsychiatric disorders, including Alzheimer disease, schizophrenia, and major depression. A major confounder in molecular studies using human brain tissue is postmortem interval (i.e. the amount of time between a subject's death and processing of tissue). We examined the integrity of biomolecules that were of interest to molecular studies of neurologic disorders, including RNA, microRNA, histone modifications, and proteins, at various postmortem intervals in an animal model to assess their robustness and suitability for experimentation. Sprague-Dawley rats were selected as model and subjected to 2 conditions: a variable postmortem interval at room temperature and a fixed time of 24hours at 4°C, which simulates the period commonly spent in the morgue before brain collection. Eight time points were investigated. MicroRNA was impressively resistant to postmortem intervals; methylated histone modifications showed a threshold between 72 and 96 hours, mirroring results from histone proteins at 72 hours. RNA degradation was transcript-specific, with housekeeping genes being more robust than genes with lower expression. Our results suggest that molecules commonly investigated in genetic and epigenetic studies were highly stable through the postmortem intervals investigated. These results support the continued use of postmortem tissue for neuropsychiatric research.